Application of Anfis-Pid Controller for Statcom to Enhance Power Quality in Power System Connected Wind Energy System - Vinh, Nguyen, Huu; Nguyen, Hung; Le, Kim Hung (International Journal of Engineering and Technology, 2018)
In this paper, a proposed ANFIS-PID controller for the STATCOM to improve transient stability of the power system including DFIG based wind farm based on their nonlinear modeling is presented. The comparative simulation results in two cases of no controller and the ANFIS-PID controller for the STATCOM when occurs a three-phase short-circuit fault in the studied multi-machine power system are shown. It is shown the effectiveness of the proposed ANFIS-PID controller and applicability to a practical power system for enhancing power quality in transient time under large disturbance.Â Â